Aplikasi Konsep Rekreatif pada Perencanaan Desain Budidaya dan Pengolahan Aren di Tuban - Pamungkas, Danny Tri; Laksono, Sigit Hadi; Nareswarananindya, Nareswarananindya (Tekstur (Jurnal Arsitektur), 2021)
Abstract. Palm tree (Arenga pinnata Merr.) is a multipurpose tree and it has been known that palm tree produces industrial materials. In East Java, palm plant spreads in all of north coast, especially in Tuban. Based on the problem, Palm Cultivated and Processing Center is designed to support government's plans and programs in the develop of the first cultivation and processing palm plant in Indonesia with the theme of Agro-tourism. The design concept is "Recreational" which is something that can provide entertainment that is creative, unique, and different from the others. So that a design will provide pleasant entertainment. The purpose of this article is as a Palm Cultivation and Processing Center in Tuban where there are facilities such as cultivation land along with processing and outdoor tourism facilities such as Flying Fox and Playground.Keywords: Aren, Cultivation, Recreational.Â Abstrak. Pohon Aren (ArengaÂ  pinnataÂ  Merr.)Â  adalahÂ  pohonÂ  serbaguna yang sejak lama telah dikenal menghasilkan bahan-bahan industri. Tanaman Aren di Jawa Timur tersebar di seluruh pesisir pantai utara khususnya di daerah Tuban. Berdasarkan permasalahan diatas, Pusat Budidaya dan Pengolahan Aren dirancang untuk mendukung program dan rencana pemerintah dalam upaya pengembangan budidaya dan sekaligus pengolahan aren pertama di Indonesia yang bertema agrowisata. Konsep desain adalah â€œRekreatifâ€ merupakan sesuatu yang dapat memberikan hiburan yang kreatif, memiliki keunikan, dan berbeda dengan yang lain. Sehingga sebuah rancangan akan memberikan hiburan yang menyenangkan. Tujuan dari artikel ini sebagai Pusat Budidaya dan Pengolahan Aren di Tuban yang mana terdapat fasilitas seperti lahan budidaya beserta pengolahan dan sarana wisata outdoor seperti Flying Fox dan Playground.Kata Kunci: Aren, Budidaya, Rekreatif